In situ XANES study of the influence of varying temperature and oxygen fugacity on iron oxidation state and coordination in a phonolitic melt - Le losq, Charles; Moretti, Roberto; Oppenheimer, Clive; Baudelet, François; Neuville, Daniel (Contributions to Mineralogy and Petrology, 2020)
International audience Iron oxidation state and environment in magmas affect their phase diagram and their properties, including viscosity and density, which determine magma mobility and eruptive potential. In turn, magma composition, pressure, temperature and oxygen fugacity affect iron oxidation state and coordination, potentially leading to complex feedbacks associated with magma ascent, degassing and eruption. While equilibrium experiments and models have led to a deep understanding of the role of iron in melts, our knowledge of the effects of disequilibrium processes on iron oxidation state and its structural role in lavas and magmas remains limited. Accordingly, we performed a series of dynamic disequilibrium experiments on a natural melt composition (a phonolite lava from Erebus volcano, Antarctica) at atmospheric pressure, in which oxygen fugacity and temperature were controlled and varied. During the experiments, we continuously measured iron oxidation and coordination using Fe K-edge dispersive X-ray Absorption Spectroscopy (XAS). We found that iron oxidation state changes in the phonolite melt are reversible and well reproduced by existing models. Changes in iron oxidation state are driven by joint diffusion of alkali cations and oxygen anions at magmatic temperatures (~ 1000 °C for Erebus phonolite). However, redox diffusion timescales are too slow for any significant oxygen exchange with the atmosphere at the lava/air interface or via air entrainment. Turning to iron coordination, while Fe 2+ and Fe 3+ are present mostly in an average five-fold coordination, complex coordination variations decoupled from redox changes were detected. The data suggest transitions between Fe 3+ in four-fold and six-fold coordination prior to reduction or as a consequence of oxidation. This questions the possible implication of Fe coordination changes in triggering crystallisation of magnetite nanolites upon magma ascent, and, through such crystallisation events, in promoting magma explosivity.